Hulless Barley: A new era of research for food purposes - Shaveta, S; Kaur, Harinderjeet; Kaur, Simarjit (Journal of Cereal Research, 2019)
Barley (Hordeum vulgare L.) is included in the family of grasses and is the fourth highly significant crop after maize, wheat, and rice. Barley is considered as an important food ingredient because of the presence of vital biochemical constituents viz. β-glucan, starch, amylose, protein etc. Barley is usually classified as hulless or hulled types (absence or presence of hull adheringto grain). Hulless barley needs negligible processing and preserves the maximum of the endosperm and germ, which is once in a while lost during the time spent for dehulling. As a result, it is highly suitable for human utilization, as the entire grain can be specifically utilized to form a meal or processed into flour. Interest in the use of hulless barley as a food grain has expanded primarily due to its stated health benefits. The regular intake of hulless barley contributes to the maintenance of normal blood cholesterol level, beneficial in preventing certain types of cancer like colon cancer and also provides better glucose and insulin responses. Hulless barley has high β-glucan content which helps in lowering of glycemic index and also causes the stimulation of bowel health. For this reason, the food industry is anxious about expanding the utilization of these cereals as nourishment fixings and henceforth more research is merited here. DOI.org/10.25174/2249-4065/2019/83719